Rebuilding Communities After Displacement Sustainable and Resilience Approaches - Hamza, Mo.; Amaratunga, Dilanthi; Haigh, Richard; Malalgoda, Chamindi; Jayakody, Chathuranganee; Senanayake, Anuradha (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book presents a collection of double-blind peer reviewed papers under the scope of sustainable and resilient approaches for rebuilding displaced and host communities. Forced displacement is a major development challenge, not only a humanitarian concern. A surge in violent conflict, as well as increasing levels of disaster risk and environmental degradation driven by climate change, has forced people to leave or flee their homes - both internally displaced as well as refugees. The rate of forced displacement befalling in different countries all over the world today is phenomenal, with an increasingly higher rate of the population being affected on daily basis than ever. These displacement situations are becoming increasingly protracted, many lasting over 5 years. Therefore, there is a need to develop more sustainable and resilient approaches to rebuild these displaced communities ensuring the long-term satisfaction of communities and enhancing the social cohesion between the displaced and host communities. Accordingly, chapters are arranged around five main themes of rebuilding communities after displacement. Response management for displaced communities. The Built environment in resettlement planning Governance of displacement Socio-Economic interventions for sustainable resettlement · .
Rebuilding After Displacement: Identifying the Needs of Displaced Communities from the Perspective of the Built Environment -- Micro-narratives on People's Perception of Climate Change and its Impact on Their Livelihood and Migration: Voices from the Indigenous Aymara People in the Bolivian Andes -- From Zero to Hero? Changes in the Estonian Context for Refugees -- Challenges of Resilience Building Among Traditional Agricultural Communities Displaced by the Landslides -- Displaced Fishermen off the Coast: Impact of Multiple Hazards on Life Above the Water -- Drivers of Slow-onset Displacement in the Coastal Mid-Atlantic Region and Preferences for Receiving Locations -- Living with Landslide Risks: A Case of Resistance to Relocation Among Vulnerable Households Residing in the Kegalle District of Sri Lanka -- Internal Displacement in Nigeria: What are the Preventive Measures? -- An Architectural Analysis of Tsunami Re-settlement Villages of South of Sri Lanka -- Forced Displacement Following Reconstruction Approaches After 2005 Zarand Earthquake, Iran -- Disaster Induced Relocation of Vulnerable Households: Evidence from Planned Relocation in Sri Lanka -- How are Tamil Villages Reconstructed? Ethnography of Place-Making in Post-war Reconstruction in Sri Lanka -- Reproducing Vulnerabilities Through Forced Displacement: A Case Study of Flood Victims in Galle District, Sri Lanka -- Verticalised Slums, Governmentality and Pandemic Governance: A Critical Hermeneutical Analysis of Governance Practices in a Selected Urban High-Rise in Colombo, Sri Lanka -- Policy Recommendations for Built Environment Professional Bodies in Upgrading their Professional Competencies to Address Displacement Contexts -- Socio-economic Effects of War Against Terror Induced Displacement on Host Communities in District Kohat, Pakistan -- Social Capital and Community Organizing in Community-Based COVID-19 Management in Two Resettlement Sites in the Philippines -- A Guideline for Host Communities in Selecting Effective Livelihood's Interventions for Refugees in An Informal Refugee Resettlement: A Case Study of Chiang Mai Province, Thailand -- Changes in Social Capital After the 2011 Great East Japan Earthquake - Results of an Awareness Survey in Taro district, Miyako City, Iwate Prefecture -- The Role of Social Capital as a Post-Relocation Coping Mechanism: A Case Study of Kegalle, Sri Lanka -- Relocated or Displaced? A Social Inquiry of Tsunami Induced Relocation Programme in Southern Sri Lanka -- Migrants and Resettlement: Mobilising Co-Existence through Social Cohesion.
Keywords: Social sciences; Culture; Human rights; Sustainability; Society; Global and International Culture; Human Rights; Sustainability